2017
DOI: 10.1111/jcpe.12793
|View full text |Cite
|
Sign up to set email alerts
|

A double‐masked Randomized Clinical Trial (RCT) comparing four periodontitis treatment strategies: 5‐year clinical results

Abstract: While single-level analyses showed statistically significant differences, they could not be confirmed with more appropriate analyses and were too small to recommend MTZ, with its risk of patient side effects and environmental consequences, for the treatment of patients with severe periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 58 publications
2
35
0
7
Order By: Relevance
“…Recently, we published the latest results from a longitudinal intervention study in which a 3‐month rigorous oral hygiene phase preceded the interventions (Preus, Gjermo, & Baelum, ). This approach to periodontal therapy planning was later reviewed by Özbozdoganli, Findik, and Müezzinoglu, (), who concluded that the 3‐month oral hygiene phase before the intervention was a limitation of the study since this procedure did not “corroborate with everyday clinical practice, making it difficult to extract conclusions.” If this is the perception among dental clinicians and periodontal specialists, relevant literature must be consulted to establish why.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we published the latest results from a longitudinal intervention study in which a 3‐month rigorous oral hygiene phase preceded the interventions (Preus, Gjermo, & Baelum, ). This approach to periodontal therapy planning was later reviewed by Özbozdoganli, Findik, and Müezzinoglu, (), who concluded that the 3‐month oral hygiene phase before the intervention was a limitation of the study since this procedure did not “corroborate with everyday clinical practice, making it difficult to extract conclusions.” If this is the perception among dental clinicians and periodontal specialists, relevant literature must be consulted to establish why.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Reduction of inflammatory symptoms prior to therapy will influence on intervention protocol (Morrison, Ramfjord, & Hill, ). (b) Mastering oral hygiene prior to periodontal therapy is essential for the maintenance phase, in which the patient must exercise rigorous oral hygiene to prevent recurrence (Preus et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations